2012
DOI: 10.1021/la2042839
|View full text |Cite
|
Sign up to set email alerts
|

New Functionalizable Alkyltrichlorosilane Surface Modifiers for Biosensor and Biomedical Applications

Abstract: We report herein three unprecedented alkyltrichlorosilane surface modifiers bearing pentafluorophenyl ester (PFP), benzothiosulfonate (BTS), or novel β-propiolactone (BPL) functionalizable terminal groups. Evidence is provided that these molecules can be prepared in very high purity (as assessed by NMR) through a last synthetic step of Pt-catalyzed alkene hydrosilylation then directly employed, without further purification, for the surface modification of quartz and medical grade stainless steel. Subsequent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 21 publications
3
24
0
Order By: Relevance
“…Recent studies related to increasing of interaction efficiency to organically derivatized silica, have shown that this can be achieved by incorporating non-reactive silanes [17]. The capacity of functionalization with trialkoxysilane [5,6,7,8,9,10] or monoalkoxysilane derivatives was previously studied [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies related to increasing of interaction efficiency to organically derivatized silica, have shown that this can be achieved by incorporating non-reactive silanes [17]. The capacity of functionalization with trialkoxysilane [5,6,7,8,9,10] or monoalkoxysilane derivatives was previously studied [10].…”
Section: Introductionmentioning
confidence: 99%
“…28), 34) In this study, physical and covalent incorporation of 1 mol % dimethylaminonathylsulfonamide (dansyl) dyes 13 was used to prepare fluorescent silica particles. Dansyl dyes, widely used for bio-medical applications, 37) non-linear optical materials, 40) membranes, 7) and for preparing fluorescent nanoparticles 38)41) are readily modified through the sulfonamide functionality with one or two 3-(triethoxysilyl)propyl groups, making them perfect candidates to investigate the influence of the number of trialkoxysilyl groups on dye incorporation, leaching and photochemical stability. For physical encapsulation, hollow silica particles (E-DA) containing N-propyldansylamide 1 in their core were prepared by inverse-emulsion polymerizations of TEOS (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Quite a large variety of head functions has been described in the literature with respect to trichlorosilane surface chemistry . Recently, we expanded the available arsenal with the introduction of the benzenethiosulfonate moiety (−S–SO 2 –Ph) . Also reported in this study was the synthesis of a novel alkyltrichlorosilane cross‐linker bearing a readily functionalizable pentafluorophenyl (PFP) ester head group .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we expanded the available arsenal with the introduction of the benzenethiosulfonate moiety (−S–SO 2 –Ph) . Also reported in this study was the synthesis of a novel alkyltrichlorosilane cross‐linker bearing a readily functionalizable pentafluorophenyl (PFP) ester head group . This molecule, co‐deposited with a shorter trichlorosilylalkane ‘diluent’, was next employed with success in the surface modification of quartz .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation